Mathematics Teachers Attitude Towards The Use Of Multichioce Resource Centre For Instruction In Ogun State - Olafare Festus Oladimeji (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2019)
The purpose of the study was to determine the attitude of Mathematics teachers towards the use of Multi- choice Resource Centres in Ogun State. A researcher designed questionnaire was administered to 35 Mathematics teachers in 20 secondary schools. Data obtained were analysed using percentage and mean. The study revealed that Mathematics teachers always use the technology tools provided at the Multi choice resource centre. Mathematics teachers also showed a positive attitude towards the use of the technology tools at the Multi- choice Resource Centres. The study concluded that the attitude of Mathematics teachers towards the use of the Multi- choice Resource Centres in Ogun State helps the usage. The study recommended among others that Multi- choice Resource Centres should be put in place in other schools and continuous training should be organized for the teachers.